Anatomical analysis of the freestyle arm stroke - Mefferd, K.; Egly, E. (2001)
This web site was completed as our project in SPME 400, Functional Anatomy and Kinseiology, at Pepperdine University during the fall semester of 2001. The objective of this site is to present a scientific analysis of the muscular activity responsible for the movements in the freestyle stroke cylcle. In addition, this site contains training exercises for the development of the muscle groups involved in these movements. At this site you find further information relating to the upper extremity kinematics of the freestyle arm stroke.